(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The reinforcing effect of emphasizers can hardly be denied, hence their importance , hence the justification for writing this paper. As a particular type of adverbials , emphasizers form part of a major syntactic class. This study, thus, introduces the topic by first discussing a grammatical category characterized by being mobile and optional. The paper duly shows the scaling effect of emphasizers, their kinds and the transformational selectional rules that are operative in moving them to the right or left of the VP. It also handles their syntactic role as modifiers, their syntactic features,their occurrence or non- occurrence with negation and imperative and the position they occupy in the sentence. The paper also dwells on the agreement restrictions on emphasizers .These constraints are shown to connect with the possible semantic interpretation of the sentence in which they occur. It also tackles the particular requirements called for by emphasizers.